Pembangunan Berbasis Identitas Budaya Nasional - Victor Silaen (Yayasan Bina Darma, 2015)
Develops the nation is mean develop it human being. Develops human being is mean improves its culture. Because that basic, so the progress of a nation basically is re;lection of super power of it culture. So, how far the progress of economic, political, and all of progress that received a nation is depend on cultural value that preservation by its nation. For it, in the future, Indonesia must be create a cultural developing as most vital agenda and urgent agenda. It is mean all of policy of the government must be oriented to make good education and enlighten society over the education sector or other sector. Education is not just formal kind (school/higher education) but also non formal education (out of school or higher education). Because, through the education logic and potential of human being can be improved. And, if both of it improving can cause human being be creative and innovative. This is the big and important capital in development. In other side, Indonesian nationalism also must be stabilizing, and must be based on democracy that facilited the same participation space to every person in society and honour the human right and law. Keywords:Culture, the values of culture, religion, national culture, evelopment.